2018
DOI: 10.1007/s13224-018-1129-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of Maternal Mortality at a Tertiary Care Hospital: What Have we Achieved?

Abstract: Background Mothers are the nurturing pillar of the family. When a woman dies or becomes ill, either during or after giving birth, the consequences have the potential to affect not only the woman herself, but her family, society and the nation as well.Objectives The study was designed to evaluate the maternal mortality ratio in a tertiary care hospital, assess the demographic profile, causes of maternal mortality, type Pratima Mittal is a Professor and Head of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
15
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 5 publications
8
15
2
Order By: Relevance
“…Earlier studies have also reported similar reasons for increased maternal deaths. 9,10 Majority of the death (37.5%) was observed in 20-24 years of age which is consistent with earlier studies and the national data. 3,6,8,10 Present study reported an equal proportion of maternal deaths in primipara and multipara.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Earlier studies have also reported similar reasons for increased maternal deaths. 9,10 Majority of the death (37.5%) was observed in 20-24 years of age which is consistent with earlier studies and the national data. 3,6,8,10 Present study reported an equal proportion of maternal deaths in primipara and multipara.…”
Section: Discussionsupporting
confidence: 91%
“…3 The MMR in this study is comparable to the results of Sundari et al (802) but very high in comparison to the other previous studies. [6][7][8][9] The high maternal mortality ratio in the present study can be explained by the fact that our centre is a tertiary referral centre attending large number of referred complicated cases and most of the patients are referrals from distant places. Most of the cases presented at late stage with serious complications (66.07%) and expired within 24 hours of admission (53.57%).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Remarkably the great majority of women who died had attended some form of ANC, while only 7.2% did not attended even once. This is paradoxical to other studies, in which most maternal deaths occurred in unbooked women [33][34][35]. This paradox is in agreement with official reports of the Egyptian ministry of health and may be explained from the point of view that women with high risk pregnancies receive ANC while women with low risk pregnancies do not book for ANC.…”
Section: Discussionsupporting
confidence: 70%